Uma investigação funcionalista dos meios de expressão das relações retóricas de causa e resultado em elocuções formais - Mamus, Priscilla Teixeira (2009)
The aim of this paper is to describe how the rethorical relations cause and result are expressed in formal elocutions (lectures). By the Rethorical Structure Theory aplication, functional theory developed by Mann e Thompson (1987) which describes the established relations between the parts from a text, it's intended to verify the relations cause and result relevance in a construction of a discourse which are proposed to explain and teach, according to its kind of mark in a particular lecture context. The relations were indetified in the corpus, and after they were classified's the sort of mark. Then, it was observed how de relations were applied to the lectures, who were the informers, got their comunicatives purpose. The research corpus is formed by 10 formal elocutions (lectures) which belong to Funcpar (Functional Research Group on North/ North-East of Paraná) database. The subjects of the research are university lecturers who were born in Maringá (PR) or have lived in it for at least 10 years. The data were recorded during graduation classes and were transcribed according to a pattern based on NURC project (PRETI, 1993, p. 11-12) with a few adaptations. The segmentation of the units of the corpus followed Chafe's (1987) concept of intonation units. Results indicate the analysis of the cause and result relations in the teachers' speech not only contributed to their purpose of teaching, but also with the bent of the students interpretation in front of the teachers. explanations and communicative goals. This is because both the cause and results help in explaining subjects, because they seem to facilitate the understanding by students, since it is easier to understand a result when its cause is presented. Results of the research have showed a contribution with researches about textual organization, mainly the oral discourse, because the text producer, according to its genre, can influence not only in its coherence and compreension, but also to the purposes which the text producer aims to get. The description of this relations' ways of comunication can serve as base to researches about texts' automatic generation and interpretation in Computational Linguistic and also to the textual production tools.